Halloween - Gibbons, Gail (New York : Holiday House, 1984)
Presents the many traditions associated with the Halloween holiday, including making jack-o-lanterns, wearing costumes, trick-or-treating, and telling scary stories
Keywords: Halloween - Juvenile literature; Halloween